Atmospheres of engagement within a German drug consumption room. (May 2020) - Duncan, Tristan; Sebar, Bernadette; Lee, Jessica; Duff, Cameron
Abstract: Drug consumption rooms directly attempt to intervene in and govern the place and time of drug use. Whilst the risk-reducing potentials of these interventions have been thoroughly evaluated, the consumption room literature offers fewer insights into the embodied, affective and situated dynamics that underscore service delivery. In this paper, we take up the notion of atmosphere to explore these dynamics in greater depth. Drawing on 12 months of ethnographic research in a German drug consumption room, we describe the manner in which atmospheres came to pervade and condition service encounters. More than simply providing texture to activities within the consumption room, we show how atmospheres gave rise to a distinct range of bodily capacities and therapeutic effects. Critically, these atmospheric affordances exceeded the risk-reducing objectives of the consumption room to encompass an emergent capacity to find repose, enact respite and foster modes of sociality and care. Our analysis further highlights the contextual contingencies through which the atmospheres of the consumption room emerged, including the efforts of both staff and clients to cultivate and control particular atmospheric qualities. We conclude by considering how closer attention to the atmospheric and affective dimensions of service delivery may challenge how consumption room interventions are enacted, valued and researched. This is to gesture towards a novel, atmospheric mode of harm reduction that has effects by transforming embodied potentials for both staff and clients. Highlights: Uses ethnography to explore the atmospheric dimensions of a drug consumption room. Describes how atmospheres emerge through and shape service encounters. Analyses how atmospheres mediate the expression of care and support. Shows how staff and clients cultivate and control particular atmospheric qualities. Gestures towards the possibilities of and for an atmospheric harm reduction.